Profound perturbation induced by triclosan exposure in mouse gut microbiome: a less resilient microbial community with elevated antibiotic and metal resistomes - Bei Gao; Pengcheng Tu; Xiaoming Bian; Liang Chi; Hongyu Ru; Kun Lu (BMC, 2017)
Abstract Background Environmental chemical-induced perturbations of gut microbiome are associated with a series of adverse health outcomes. The effects of triclosan on human health have been controversial in recent years. The purpose of this study is to investigate the functional impact of triclosan on the mouse gut microbiome and the link between triclosan exposure and resistomes in gut bacteria. Methods We combined 16S rRNA gene sequencing and shotgun metagenomics sequencing to examine the compositional and functional impact of triclosan exposure on the gut microbiota of C57BL/6 mice. Results 16S rRNA sequencing results revealed that 13-week triclosan exposure in drinking water induced significant perturbations in mouse gut bacterial assemblages with distinct trajectories compared to controls. Metagenomics sequencing results indicated a remarkable enrichment of gut bacterial genes related to triclosan resistance, stress response, antibiotic resistance and heavy metal resistance. Conclusions Triclosan exposure has a profound impact on the mouse gut microbiome by inducing perturbations at both compositional and functional levels. To our best knowledge, this is the first evidence regarding the functional alterations of gut microbiome induced by triclosan exposure, which may provide novel mechanistic insights into triclosan exposure and associated diseases.